Körper und christliche Lebensweise Clemens von Alexandreia und sein Paidagogos - Pujiula, Martin (Millennium-Studien / Millennium Studies, 2012)
The authorexamines the historical context of instructions for the everyday conduct of prosperous Christians and the authors of these instruction manuals from 200 AD and links this examination with a study of attitudes towardsthe human body as revealed in the instructions. The volume shows how, far from denying the body, the standards relating to health display a legitimate concern for bodily well-being. At the same time, however, there is a fear of the body, which makes it necessary to keep it constantly under control. Key Features it makes a contribution to the intensive research at present being conducted into the "Second Sophistic" it combines historical, philological, and theological methods and insights it is also of relevance for the history of medicine.